Gut microbiota can utilize prebiotic birch glucuronoxylan in production of short-chain fatty acids in rats. Issue 6 (10th March 2022) - Kynkäänniemi, Emma; Lahtinen, Maarit H.; Jian, Ching; Salonen, Anne; Hatanpää, Timo; Mikkonen, Kirsi S.; Pajari, Anne-Maria
Abstract : Birch-derived polyphenol and fiber (glucuronoxylan, GX)-rich extract and highly purified GX-rich extract support the growth of beneficial gut bacteria, suppress the harmful ones, and increase the production of total short-chain fatty acids (SCFA). Abstract : Birch-derived glucuronoxylan (GX)-rich hemicellulose extract is an abundantly available by-product of the forest industry. It has multifunctional food stabilizing properties, and is rich in fiber and polyphenols. Here, we studied its effects on colonic metabolism and gut microbiota in healthy rats. Male and female Wistar rats ( n = 42) were fed AIN-93G-based diets with 10% (w/w) of either cellulose (control), a polyphenol and GX-rich extract (GXpoly), or a highly purified GX-rich extract (pureGX) for four weeks. Both the GXpoly and pureGX diets resulted in changes on the gut microbiota, especially in a higher abundance of Bifidobacteriaceae than the cellulose containing diet ( p < 0.001). This coincided with higher concentrations of microbial metabolites in the luminal contents of the GX-fed than control rats, such as total short-chain fatty acids (SCFAs) ( p < 0.001), acetate ( p < 0.001), and N-nitroso compounds (NOCs) ( p = 0.001). The difference in the concentration of NOCs was not seen when adjusted with fecal weight. GX supplementation supported the normal growth of the rats. Our results indicate that GXpoly and pureGX can favorably affect colonic metabolism and the gut microbiota. They have high potential to be used as prebiotic stabilizers to support more ecologically sustainable food production.